The Use of the RELiZORB Immobilized Lipase Cartridge in Enterally-Fed Children With Cystic Fibrosis: A Retrospective Case Series. Issue 4 (October 2022) - Baghae Pour, Parasto; Gregg, Shannon; Coakley, Kathryn E.; Caffey, L. Francine; Cohen, Deborah; Myers, Orrin B.; Gonzales-Pacheco, Diana
Abstract : The objective of this retrospective study was to evaluate the impact of the RELiZORB immobilized lipase cartridge with overnight enteral nutrition (EN) on body mass index (BMI) or weight-for-length percentile, stool quality, and gastrointestinal (GI) symptoms in children with cystic fibrosis (CF) and pancreatic insufficiency. Frequency of diarrhea, steatorrhea, and malodorous stools significantly decreased at final visit compared with baseline ( P = .008, P = .004, P = .031, respectively). Improved BMI or weight-for-length percentile was observed in 10 out of 16 participants; however, the change was not significant. RELiZORB use decreased frequency of most GI symptoms in pediatric patients with CF on EN.